2023
DOI: 10.3390/polym15153221
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Fillers and Their Effects on the Properties of Flax/PLA Composites after UV Degradation

Moumita Sit,
Saeid Dashatan,
Zhongyi Zhang
et al.

Abstract: The present investigation seeks to assess the impact of fillers on the mechanical characteristics of entirely biodegradable composites, introducing an advanced solution to fulfil long-term durability demands within point-of-purchase (POP) industries. The inclusion of calcium carbonate (CaCO3) fillers on the various properties of the flax fibre-reinforced composites, after accelerated irradiation in an ultraviolet (UV) radiation exposure has been investigated in the present study. Different types of flax fibre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Several studies have investigated the effects of weathering on the mechanical properties of PFRP. Sit et al 22 reported that both tensile strength and modulus of the biocomposites made from nonwoven flax fiber and polylactic acid decreased by about 15% after 500‐h UV exposure and the inorganic fillers can help to alleviate the loss of mechanical properties. Hallonet et al 23 studied the difference between FFRP and glass fiber‐reinforced polymer (GFRP) after aging and claimed that the FFRP lost 15% tensile strength during weathering aging in the outdoor environment for 12 months, while the tensile properties of GFRP remain stable.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the effects of weathering on the mechanical properties of PFRP. Sit et al 22 reported that both tensile strength and modulus of the biocomposites made from nonwoven flax fiber and polylactic acid decreased by about 15% after 500‐h UV exposure and the inorganic fillers can help to alleviate the loss of mechanical properties. Hallonet et al 23 studied the difference between FFRP and glass fiber‐reinforced polymer (GFRP) after aging and claimed that the FFRP lost 15% tensile strength during weathering aging in the outdoor environment for 12 months, while the tensile properties of GFRP remain stable.…”
Section: Introductionmentioning
confidence: 99%